2012
DOI: 10.1167/iovs.12-9822
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Simultaneous Negative and Positive Defocus on Eye Growth and Development of Refractive State in Marmosets

Abstract: Imposing hyperopic and myopic defocus simultaneously using concentric contact lenses resulted in relatively smaller and less myopic eyes, despite treated eyes being exposed to a greater percentage of negative defocus. Exposing the retina to combined dioptric powers with multifocal lenses that include positive defocus might be an effective treatment to control myopia development or progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 37 publications
(62 reference statements)
8
104
1
2
Order By: Relevance
“…It has been shown that presenting chick eyes with simultaneously competing myopic and hyperopic defocus, using either mixed astigmatic (toric) lenses with opposite lens powers on the two perpendicular meridians (McLean and Wallman 2003), lens-cone devices with two target planes (Diether and Wildsoet 2005) or dual-power lenses that had different combinations of lens powers (Tse et al 2007), caused hyperopia, confirming the dominating effect of myopic defocus in chicks. Moreover, Benavente-Perez et al (2012) reported similar results in marmosets by using multi-zone contact lenses with alternating powers. Therefore, it seems that when the retina experiences myopic and hyperopic defocus simultaneously, myopic defocus still dominates compensation, although to a smaller degree than when the eye experiences myopic and hyperopic defocus in succession.…”
Section: Integration Of Simultaneous Myopic and Hyperopic Defocusmentioning
confidence: 55%
“…It has been shown that presenting chick eyes with simultaneously competing myopic and hyperopic defocus, using either mixed astigmatic (toric) lenses with opposite lens powers on the two perpendicular meridians (McLean and Wallman 2003), lens-cone devices with two target planes (Diether and Wildsoet 2005) or dual-power lenses that had different combinations of lens powers (Tse et al 2007), caused hyperopia, confirming the dominating effect of myopic defocus in chicks. Moreover, Benavente-Perez et al (2012) reported similar results in marmosets by using multi-zone contact lenses with alternating powers. Therefore, it seems that when the retina experiences myopic and hyperopic defocus simultaneously, myopic defocus still dominates compensation, although to a smaller degree than when the eye experiences myopic and hyperopic defocus in succession.…”
Section: Integration Of Simultaneous Myopic and Hyperopic Defocusmentioning
confidence: 55%
“…Normal refractive development has been observed in light levels that have ranged upwards from 60 lux (Ehrlich et al, 1990) to 700 lux (Benavente-Perez et al, 2012; Li et al, 2000) but more typically have been in the 250 to 500 lux range (Ashby et al, 2010; Backhouse and Phillips, 2010; Callahan and Petry, 2000; Crewther and Crewther, 2002; Dong et al, 2011; Feldkaemper et al, 1999; Iuvone et al, 1978; Leech et al, 1995; McCarthy et al, 2007; Metlapally and McBrien, 2008; Smith et al, 2012; Vessey et al, 2005). The lights typically are on for 12 or 14 hours per day and off the remaining time.…”
Section: Animal Studiesmentioning
confidence: 99%
“…24,26,[31][32][33][34][35][36][37] Smith et al, 26 in particular, argued for a role of the peripheral retina in central refractive control when they showed that, in primates with and without functioning central retina, negative defocus lenses applied in a peripheral annulus still led to myopia development. Stone et al 31 established that different sizes of central or peripheral apertures in opaque goggles led to varying levels of myopia and increases in axial length in chickens.…”
Section: Discussionmentioning
confidence: 99%